Using Google Docs as A Collaborative Writing Medium For Empowering Senior High School Students' Writing Skills - Dinda Purna Putri; Anis Trisusana (Fakultas Ilmu Budaya, Universitas Brawijaya, 2022)
This study investigates the effect of using Google Docs online learning media in conjunction with collaborative writing strategies on high school students' writing skills. The study took place at Surabaya's high schools, with 16 tenth-grade students participating. The research is a pre-experimental design with a one-group pretest and posttest design. The study's design involved only one class in the treatment of Google Docs media in collaborative writing. The first research question focused on implementing Google Docs and collaborative writing activities in the learning process conducted by a teacher and students. The findings were determined from observational sheets. Further research findings for the second research question, which were derived from students’ pre-test and post-test scores, were examined using t-tests and presented quantitatively. Additionally, questionnaires were used to determine students' perceptions of the use of Google Docs as a collaborative medium in their writing studies. According to research findings, students' scores improved significantly following treatment compared to their pre-treatment scores. Cohen's d was used to determine the magnitude of the effects created by this study, and it was discovered that the effects were quite significant. The results for the second research question indicated that the learning process was done successfully. Students' attitudes towards the treatment also showed that most groups performed well during the activity. Furthermore, the third research question results indicated that the combination of Google Docs and collaborative writing methods elicited favorable responses from students. Thus, collaborative writing strategies utilizing Google Docs as a medium can assist Senior High School students in writing more effectively.